2014
DOI: 10.1016/j.ijdevneu.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of colostrum and plasma immunoglobulin intake on hippocampus structure during early postnatal development in pigs

Abstract: The first milk, colostrum, is an important source of nutrients and an exclusive source of immunoglobulins (Ig), essential for the growth and protection from infection of newborn pigs. Colostrum intake has also been shown to affect the vitality and behaviour of neonatal pigs. The objective of this study was to evaluate the effects of feeding colostrum and plasma immunoglobulin on brain development in neonatal pigs. Positive correlations were found between growth, levels of total protein and IgG in blood plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
(46 reference statements)
0
10
0
1
Order By: Relevance
“…It is noteworthy in this study that IF remained inferior to BC and HM, even using a relatively slow (27). Furthermore, IF products are clearly inferior to intact milk products in stimulating immunity and mucosal defense mechanisms (28)(29)(30). This study demonstrates that preterm pigs display lower physical activity level relative to term pigs over the first week of life and that a slow increase in enteral nutrition stimulates GIT growth as well as physical activity level.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…It is noteworthy in this study that IF remained inferior to BC and HM, even using a relatively slow (27). Furthermore, IF products are clearly inferior to intact milk products in stimulating immunity and mucosal defense mechanisms (28)(29)(30). This study demonstrates that preterm pigs display lower physical activity level relative to term pigs over the first week of life and that a slow increase in enteral nutrition stimulates GIT growth as well as physical activity level.…”
Section: Discussionmentioning
confidence: 58%
“…A direct neuroprotective role of colostrum is supported by the enhanced microgliogenesis and hippocampus neuron density in 3-d-old term pigs fed sow's colostrum vs. formula (28), and the colostrum-induced reduced neurological deficit in a rodent model of brain ischemia/reperfusion injury (31). As indicated above, increased physical activity in term pigs, and in MEN-fed preterm pigs, may also result from improvements in the general clinical status, secondary to enhanced nutrient absorption via improved GIT maturation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by our lab showed a positive relationship between plasma levels of IG and hippocampus development during the first 3 days of postnatal development [16]. The hippocampus is involved in memory and learning, which are processes shown to be deficient in premature infants.…”
Section: Discussionmentioning
confidence: 87%
“…The possible mechanisms of extra-immunological effects of immunoglobulins have not yet been elucidated and require further investigation, especially with regards to the development of the CNS. In fact, only one publication from our lab [16] indirectly points out the effects of absorbed immunoglobulins on brain function/development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation